The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1088/0957-4484/25/31/315201
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic-photonic crystal coupled nanolaser

Abstract: We propose and demonstrate a hybrid photonic-plasmonic nanolaser that combines the light harvesting features of a dielectric photonic crystal cavity with the extraordinary confining properties of an optical nano-antenna. For this purpose, we developed a novel fabrication method based on multi-step electron-beam lithography. We show that it enables the robust and reproducible production of hybrid structures, using a fully top-down approach to accurately position the antenna. Coherent coupling of the photonic an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…Sophisticated slotted waveguides [141,[151][152][153] as well as nanobeam cavities [140,146,150,[154][155][156][157][158][159][160] have also been implemented for analyte-specific stoichiometric studies and biomolecule micromanipulation. Extreme, sub-attomolar detection of a streptavidin protein was reported for nanoslot PhC nanolasers [139,[161][162][163][164][165][166][167][168], while novel PhC nanocavities combined with plasmonic nanostructures have emerged as hybrid photonic-plasmonic biosensors [169][170][171][172][173][174][175][176][177][178][179]. Unusually sensitive biodetection down to the single-molecule level with nanostructured materials comprising selfassembled silver nanoparticles on PhC diatom biosilica [180,181] and a gold antenna-in-a-nanocavity [182] substantiates the fast and steady advancement of hybrid photonic-plasmonic instrumentation utilising PhCs.…”
Section: Photonic Crystals Engineered With Nano/microcavities For Intmentioning
confidence: 99%
See 2 more Smart Citations
“…Sophisticated slotted waveguides [141,[151][152][153] as well as nanobeam cavities [140,146,150,[154][155][156][157][158][159][160] have also been implemented for analyte-specific stoichiometric studies and biomolecule micromanipulation. Extreme, sub-attomolar detection of a streptavidin protein was reported for nanoslot PhC nanolasers [139,[161][162][163][164][165][166][167][168], while novel PhC nanocavities combined with plasmonic nanostructures have emerged as hybrid photonic-plasmonic biosensors [169][170][171][172][173][174][175][176][177][178][179]. Unusually sensitive biodetection down to the single-molecule level with nanostructured materials comprising selfassembled silver nanoparticles on PhC diatom biosilica [180,181] and a gold antenna-in-a-nanocavity [182] substantiates the fast and steady advancement of hybrid photonic-plasmonic instrumentation utilising PhCs.…”
Section: Photonic Crystals Engineered With Nano/microcavities For Intmentioning
confidence: 99%
“…Computational analysis pinpointed parameters/dimensions for an ultrahigh Q/V ratio and hence conditions conducive for trapping and micromanipulation. The experimental realisation of a hybrid nanolaser that uses the coupling between a LSPR of a bowtie and photonic mode of an active PhC with a L7 microcavity is visible in Figure 30C-H [179]. The fabrication approach is also flexible in terms of variability of scale and morphology as is demanded by the constraints imposed by the analyte.…”
Section: Photonic Crystals Engineered With Nano/microcavities For Intmentioning
confidence: 99%
See 1 more Smart Citation
“…One of their interesting features is their ability to focus light at the nanometer scale, leading to strong local fields (called hot spots) near the metal surfaces [4,5]. The fact that the energy of LSPRs can be tuned through variation of the shape, the size, the composition, or the environment of the metal NPs [3,6,7] has opened the way to applications within the domains of biosensing [8], Raman spectroscopies [9,10], solar cells [11], near-field imaging [12], enhanced fluorescence spectroscopy [9], and nanolasers [13]. In addition, plasmonic excitations often play an important part in optical metamaterials [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (i.e., artificially structured materials with a unit structure considerably smaller than the wavelength of visible light [34]), like those in negative optical index materials [14,15], materials for superresolution applications [17][18][19][20], and electromagnetic cloaks [21].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid plasmonic-photonic devices were reported in 2014 for lasing (Zhang et al 2014) and light matter coupling (Michael et al 2010). In 2014, ODell et al reported a technique for assembling photonic-plasmonic nanotweezers by optically guiding multiwalled carbon nanotubes to attach them onto a silicon waveguide (ODell et al 2014).…”
Section: Introductionmentioning
confidence: 99%